A New Global Estimation of Medicinal and Aromatic - Brinckmann, J. A.; Kathe, W.; Berkhoudt, K.; Harter, D. E.; Schippmann, U.
Historically, the majority of medicinal and aromatic plant (MAP)species has been harvested in the wild. In recent decades, there has been concern that certain species appear to face threats due to overexploitation related to increasing global demand coupled with loss of habitat due to development and land use change. Earlier studies estimated that about 900 species were produced, to some extent, by cultivation. This study aims to update previous estimates by applying a systematic approach for obtaining data from a large number of different sources of information and knowledge. A broad categorization scheme for forms of cultivation is introduced. Using multiple methods of data collection, we found evidence of commercial cultivation of 3,227 taxa, belonging to 235 different plant families. The most frequently identified forms of cultivation were agroforestry, intensive farming, and controlled cultivation, followed by, to a much lesser extent, extensive farming, and natural fostering. Of the identified species, 954 have a global International Union for Conservation of Nature (IUCN)Red List assessment, of which 82 species (2.5 percent)are threatened to some degree according to IUCN Red List categories and criteria. Of the 3,227 cultivated taxa, 1,732 (54 percent)have also been assessed by national red lists, of which 688 taxa are assessed as threatened in at least one country. Additionally, 109 of the 3,227 cultivated species are included in the Convention on International Trade in Endangered Species (CITES)Appendices. The results of this research show that the number of cultivated plants is significantly higher than previously estimated. Potential consequences of threat status on the domestication of MAP species are discussed.
Keywords: DOMESTICATION; MEDICINAL CROPS; NATURAL FOSTERING; SUSTAINABLE AGRICULTURE; THREATENED SPECIES; MAP CULTIVATION; NTFP; ENRICHMENT PLANTING; CONSERVATION